2009
DOI: 10.1016/j.jalz.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves cognition and hippocampal plasticity in APOE ɛ4 mice

Abstract: Background Human studies on exercise, cognition, and apolipoprotein E (APOE) genotype show that ε4 carriers may benefit from regular physical activity. Methods We examined voluntary wheel-running, memory, and hippocampal plasticity in APOE ε3 and APOE ε4 transgenic mice at 10–12 months of age. Results Sedentary ε4 mice exhibited deficits in cognition on the radial-arm water maze (RAWM), a task dependent on the hippocampus. Six weeks of wheel-running in ε4 mice resulted in improvements on the RAWM to the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(131 citation statements)
references
References 45 publications
4
121
0
3
Order By: Relevance
“…Many studies have supported the long-term benefits of exercise in humans, even in Alzheimer's and Parkinson's patients Xu et al 2010;Erickson et al 2012;Mayeux and Stern 2012;Fisher et al 2013;Intlekofer and Cotman 2013;Winchester et al 2013). Animal studies have also shown convincingly that exercise is protective in experimental models of neurodegeneration (for some examples, see Adlard et al 2005;Nichol et al 2009;Pothakos et al 2009;Zigmond et al 2009;Gerecke et al 2010;Vuckovic et al 2010;Intlekofer and Cotman 2013;Souza et al 2013). The studies on the benefits of long term exercise, dietary phytochemicals such as nicotine and caffeine, and moderate alcohol consumption all suggest that chronic adaptation to stress may be achievable in humans.…”
Section: Adaptation and Sensitization To Proteotoxic Stressmentioning
confidence: 99%
“…Many studies have supported the long-term benefits of exercise in humans, even in Alzheimer's and Parkinson's patients Xu et al 2010;Erickson et al 2012;Mayeux and Stern 2012;Fisher et al 2013;Intlekofer and Cotman 2013;Winchester et al 2013). Animal studies have also shown convincingly that exercise is protective in experimental models of neurodegeneration (for some examples, see Adlard et al 2005;Nichol et al 2009;Pothakos et al 2009;Zigmond et al 2009;Gerecke et al 2010;Vuckovic et al 2010;Intlekofer and Cotman 2013;Souza et al 2013). The studies on the benefits of long term exercise, dietary phytochemicals such as nicotine and caffeine, and moderate alcohol consumption all suggest that chronic adaptation to stress may be achievable in humans.…”
Section: Adaptation and Sensitization To Proteotoxic Stressmentioning
confidence: 99%
“…BDNF and TrkB are highly expressed in the hippocampus. Many studies have reported that exercise increases hippocampal BDNF expression (47, 95,227) and that these increases are associated with enhanced cognition (26,143,195). Exactly what role, if any, hippocampal BDNF plays in energy metabolism is still unclear.…”
Section: Bdnf and The Central Regulation Of Energy Metabolismmentioning
confidence: 99%
“…Studies using voluntary wheel-running also reported positive effects on the BDNF tyrosine kinase B (trkB) signal transduction receptor [47,57,59,62,63]. Three studies specifically reported a positive correlation between distance run and BDNF mRNA or protein levels [60,61,65].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%